The life and scientific work of William R. Evitt (1923-2009). (13th June 2016) - Riding, James B.; Lucas-Clark, Joyce
Abstract : Occasionally (and fortunately), circumstances and timing combine to allow an individual, almost singlehandedly, to generate a paradigm shift in his or her chosen field of inquiry. William R. ('Bill') Evitt (1923-2009) was such a person. During his career as a palaeontologist, Bill Evitt made lasting and profound contributions to the study of both dinoflagellates and trilobites. He had a distinguished, long and varied career, researching first trilobites and techniques in palaeontology before moving on to marine palynomorphs. Bill is undoubtedly best known for his work on dinoflagellates, especially their resting cysts. He worked at three major US universities and spent a highly significant period in the oil industry. Bill's early profound interest in the natural sciences was actively encouraged both by his parents and at school. His alma mater was Johns Hopkins University where, commencing in 1940, he studied chemistry and geology as an undergraduate. He quickly developed a strong vocation in the earth sciences, and became fascinated by the fossiliferous Lower Palaeozoic strata of the northwestern United States. Bill commenced a PhD project on silicified Middle Ordovician trilobites from Virginia in 1943. His doctoral research was interrupted by military service during World War II; Bill served as an aerial photograph interpreter in China in 1944 and 1945, and received the Bronze Star for his excellent work. Upon demobilisation from the US Army Air Force, he resumed work on his PhD and was given significant teaching duties at Johns Hopkins, which he thoroughly enjoyed. He accepted his first professional position, as an instructor in sedimentary geology, at the University of Rochester in late 1948. Here Bill supervised his first two graduate students, and shared a great cameraderie with a highly motivated student body which largely comprised World War II veterans. At Rochester, Bill continued his trilobite research, and was the editor of the Journal of Paleontology between 1953 and 1956. Seeking a new challenge, he joined the Carter Oil Company in Tulsa, Oklahoma, during 1956. This brought about an irrevocable realignment of his research interests from trilobites to marine palynology. He undertook basic research on aquatic palynomorphs in a very well-resourced laboratory under the direction of one of his most influential mentors, William S. 'Bill' Hoffmeister. Bill Evitt visited the influential European palynologists Georges Deflandre and Alfred Eisenack during late 1959 and, while in Tulsa, first developed several groundbreaking hypotheses. He soon realised that the distinctive morphology of certain fossil dinoflagellates, notably the archaeopyle, meant that they represent the resting cyst stage of the life cycle. The archaeopyle clearly allows the excystment of the cell contents, and comprises one or more plate areas. Bill also concluded that spine-bearing palynomorphs, then called hystrichospheres, could be divided into two groups. The largely Palaeozoic spine-bearing palynomorphs are of uncertain biological affinity, and these were termed acritarchs. Moreover, he determined that unequivocal dinoflagellate cysts are all Mesozoic or younger, and that the fossil record of dinoflagellates is highly selective. Bill was always an academic at heart and he joined Stanford University in 1962, where he remained until retiring in 1988. Bill enjoyed getting back into teaching after his six years in industry. During his 26-year tenure at Stanford, Bill continued to revolutionise our understanding of dinoflagellate cysts. He produced many highly influential papers and two major textbooks. The highlights include defining the acritarchs and comprehensively documenting the archaeopyle, together with highly detailed work on the morphology of Nannoceratopsis and Palaeoperidinium pyrophorum using the scanning electron microscope. Bill supervised 11 graduate students while at Stanford University. He organised the Penrose Conference on Modern and Fossil Dinoflagellates in 1978, which was so successful that similar meetings have been held about every four years since that inaugural symposium. Bill also taught many short courses on dinoflagellate cysts aimed at the professional community. Unlike many eminent geologists, Bill actually retired from actively working in the earth sciences. His full retirement was in 1988; after this he worked on only a small number of dinoflagellate cyst projects, including an extensive paper on the genus Palaeoperidinium .